2020
DOI: 10.1038/s41598-020-77952-9
|View full text |Cite
|
Sign up to set email alerts
|

SHROOM3, the gene associated with chronic kidney disease, affects the podocyte structure

Abstract: Chronic kidney disease is a public health burden and it remains unknown which genetic loci are associated with kidney function in the Japanese population, our genome-wide association study using the Biobank Japan dataset (excluding secondary kidney diseases, such as diabetes mellitus) clearly revealed that almost half of the top 50 single nucleotide polymorphisms associated with estimated glomerular filtration rate are located in the SHROOM3 gene, suggesting that SHROOM3 will be responsible for kidney function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Interestingly, two of the three associations without genuine eGFR-decline association may relate to biomarker generation rather than kidney function: GATM and CPS1 , known for a role in creatine biosynthesis 41 and urea cycle 42 , respectively, reside in loci without supporting association with cross-sectional cystatin-based eGFR 18 . Conversely, the SHROOM3 locus was associated with cystatin-based eGFR 18 , 15 and experimental studies support a role of SHROOM3 in kidney pathology 46 48 ; thus, SHROOM3 appears to have an effect on cross-sectional kidney function, but not on kidney function decline within the limits of detectability by sample size.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, two of the three associations without genuine eGFR-decline association may relate to biomarker generation rather than kidney function: GATM and CPS1 , known for a role in creatine biosynthesis 41 and urea cycle 42 , respectively, reside in loci without supporting association with cross-sectional cystatin-based eGFR 18 . Conversely, the SHROOM3 locus was associated with cystatin-based eGFR 18 , 15 and experimental studies support a role of SHROOM3 in kidney pathology 46 48 ; thus, SHROOM3 appears to have an effect on cross-sectional kidney function, but not on kidney function decline within the limits of detectability by sample size.…”
Section: Discussionmentioning
confidence: 96%
“…While Shroom3 homozygous null mice are embryonically lethal due to exencephaly, 24 the post-natal analysis of 1-year old Shroom3 heterozygous null mice exhibit podocyte foot process effacement and kidney disease resulting from disrupted ROCK/non-muscle myosin II signaling which disrupts actin dynamics 23 . Several other studies analyzing Shroom3 genomic variants also demonstrated podocyte cytoskeletal abnormalities leading to albuminuria and CKD 25,26,27 . Altogether, these studies confirm essential roles for Shroom3 in kidney development and maintenance of kidney function.…”
Section: Introductionmentioning
confidence: 86%
“…This expression pattern in the anterior wing margin is similar to members of the Irre cell Recognition Module (IRM), including cell surface receptors Roughest, Hibris, and Kirre, which help position the sensory organs ( Linneweber et al, 2015 ). This is particularly interesting in light of the fact that the vertebrate orthologs of these genes, Neph and Nephrin-1, and Shroom3 are all involved in formation of podocytes in the glomerulus of the mammalian kidney ( Kestilä et al, 1998 ; Khalili et al, 2016 ; Matsuura et al, 2020 ; Sellin et al, 2003 ; Yeo et al, 2015 ). It will be exciting to apply genetic analysis to investigate if these pathways cooperate to regulate tissue morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, SHROOM2 has been linked to neural tube morphogenesis, colorectal cancer, and medulloblastoma ( Chen et al, 2018 ; Dunlop et al, 2012 ; Shou et al, 2015 ), while in vitro studies indicate it is important for cell migration, vasculogenesis, metastasis, and melanosome biogenesis ( Fairbank et al, 2006 ; Farber et al, 2011 ; Yuan et al, 2019 ). SHROOM3 mutations have been implicated in chronic kidney disease, heart morphogenesis, and neural tube closure in humans ( Deshwar et al, 2020 ; Durbin et al, 2020 ; Köttgen et al, 2009 ; Lemay et al, 2015 ; Matsuura et al, 2020 ; Tariq et al, 2011 ). Using model organisms or cell culture, Shroom3 has been shown to control neural tube closure, axon growth, intestine architecture, eye morphogenesis, thyroid budding, and kidney development ( Grosse et al, 2011 ; Hildebrand and Soriano, 1999 ; Khalili et al, 2016 ; Loebel et al, 2016 ; Plageman et al, 2010 ; Taylor et al, 2008 ; Yeo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%